Syagrus coronata (licuri) and Syagrus vagans (licurioba) (Arecaceae): foliar fibers and waxes of plants from two localities in Bahia - Crepaldi, Iara Cândido; Negri, Giuseppina; Salatino, Antonio; Costa Neto, Antonio (SITIENTIBUS série Ciências Biológicas, 2010)
Leaves of licuri and licurioba are exploited in rural areas of Bahia. Fibers and waxes of plants of these palm species from two localities were analyzed. Both species possess high contents of dietary total and insoluble fibers. Leaves of licuri contain significant higher contents of insoluble dietary fibers. Leaves of both species are abundant wax sources, although the contents of licuri leaves (aprox. 1.300 mg.cm-2) are significantly higher than those of licurioba (aprox. 260 mg.com-2). The present work is the first report on composition of licurioba leaf wax. Although the wax composition of licuri and licurioba is not the same, major constituents of both species are esters, alkanes and triterpenoids (lupeol, lupeyl acetate and lupenone, the latter being the most abundant). Melting point of licuri wax is relatively high (aprox. 75oC). Nonacosane is the predominant homologue in the alkane distribution of both waxes, but C30 and C31 are detectable only in licuri. Significant differences were noted in the wax contents between the populations from the two localities.